Factors influence on growth, don and niv production by two species of fusarium isolated from finger millets [eleusine coracana l.] - Vankudoth, Koteswara Rao; Penugonda, Shilpa; Sivadevuni, Girisham; Reddy, S. M. (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
ABSTRACT Objective: The present investigations (In vitro) on an influence of different synthetic and food based [flour] media, pH, temperature and microbial nutrients on growth, Deoxynivalenol [DON] and Nivalenol [NIV] production by Fusarium aethiopicum and F. culmorum was carried out. Methods: Fusarium species associated with the finger millets were isolated and identified phenotypically and further confirmed by molecular methods by Polymerase Chain Reaction [PCR]. Monosporic seven day old F. aethiopicum and F. culmorum were grown in CYA broth and incubated at 27±2°C on rotary shaker for 21 days at 120 rpm. At the end of 21 day incubation period, cultures were harvested for determination of fungal biomass. The resultant culture filtrates were extracted twice with ethyl acetate and concentrated to get and final concentration of 1 ml in methanol and employed for RP-HPLC analysis for detection of DON and NIV production. Results: Finger millets flour medium induced the highest amount of mycelial growth, DON and NIV production by F. aethiopicum. However, F. culmorum achieved highest amount of hyphal growth, DON and NIV production under the influence of yeast extract sucrose [YES] medium. Maize flour medium, rice flour medium and sorghum flour medium was next preffered substrates. Optimum pH of 5.5-6.5 and temperature of 20-35°C for growth, DON and NIV production was observed. Both the species of Fusarium failed to grow and produce toxins at pH 2.5-3.5 and temperature of 40°C. Yeast extract was most favorable for maximum DON and NIV production, which increased with an increase in its concentration. On the other hand, malt extract and beef extract induced good growth and mycotoxin production at comparatively higher concentration in both the species of Fusarium under study. Conclusion: Comparatively food based media were the better substrates than synthetic media for both growth and DOIN and NIV production by two species of Fusarium under investigation. A positive correlation coefficient [r] on growth [0.458], DON [0.744] and NIV [0.882] was recorded among the media and both the species of Fusarium. Keywords: Finger millets, F. aethiopicum, F. culmorum, Synthetic media, pH, Temperature, Microbial nutrients, DON, NIV, HPLC